Assessment of Serum Nitrogen Species and Inflammatory Parameters in Relapsing-Remitting Multiple Sclerosis Patients Treated with Different Therapeutic Approaches. (19th December 2016) - Niedziela, Natalia; Adamczyk-Sowa, Monika; Niedziela, Jacek T.; Mazur, Bogdan; Kluczewska, Ewa; Sowa, Paweł; Gąsior, Mariusz
Abstract : The role of nitric oxide and its reactive derivatives (N O x ) is well known in the pathogenesis of multiple sclerosis, which is an inflammatory disease while N O x seems to be important in coordinating inflammatory response. The purpose of the present study was to assess serum N O x as one of the nitrogen species and inflammatory parameters in relapsing-remitting multiple sclerosis patients and to compare the effectiveness of various types of disease-modifying therapies that reduce nitric oxide and inflammatory biomarkers. Elevated N O x level was observed in patients who received the first-line disease-modifying therapy (interferons beta-1a and beta-1b) in comparison with the subjects treated with the second-line disease-modifying therapy (natalizumab; fingolimod) and healthy controls without significant differences in C-reactive protein and interleukin-1 beta. A negative correlation was observed between serum N O x level and the duration of multiple sclerosis confirmed in the whole study population and in subjects treated with the first-line agents. Only serum N O x, concentration could reveal a potential efficacy of disease-modifying therapy with a better reduction in N O x level due to the second-line agents of disease-modifying therapy.